Digital Game-Based Learning in Primary Mathematics: A Systematic Review and Meta-Analysis of Research Trends and Learning Outcomes - Dwi Yulianto; Muhamad Mukri Situmeang; Astari; Rahmat Nurcahyo (RANGE: Jurnal Pendidikan Matematika, 2026)
This study presents a systematic literature review and meta-analysis of 37 empirical articles examining the implementation of Digital Game-Based Learning (DGBL) in primary school mathematics education from 2018 to 2025. Utilizing the PRISMA framework and thematic coding techniques, the study analyzes publication trends, geographical distribution, mathematical content coverage, research methodologies, as well as the types and modes of games employed. The findings indicate a significant increase in publications after 2020, with 42% originating from Asia, particularly China, Indonesia, and Malaysia. Numeracy topics, such as numbers and arithmetic operations, dominate 86% of the studies, while topics like statistics and probability remain underrepresented. Quantitative approaches, especially experimental designs, account for 68% of the methodologies used. Mini-games and individual gameplay modes are the most commonly adopted, whereas collaborative and narrative-based modes remain limited. The meta-analysis reveals that DGBL has a significant positive impact on conceptual understanding, learning motivation, and problem-solving skills. These findings highlight the importance of developing more inclusive, contextualized, and adaptive DGBL designs to strengthen foundational mathematical literacy in the digital era.